2006
DOI: 10.1111/j.1742-1241.2006.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinaemia and vascular access thrombosis among chronic hemodialysis patients in Taiwan: a retrospective study

Abstract: Vascular access thrombosis (VAT) is an important cause of morbidity for chronic haemodialysis (HD) patients. Some risk factors for VAT have been well-defined for chronic HD patients from western countries. However, only a few such factors have been confirmed for Taiwanese patients. This study attempted to determine the association between hyperhomocysteinaemia and the incidence of VAT for chronic HD patients in Taiwan. We retrospectively enrolled a total of 196 patients into this study during 2003. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…1 In the traditional view, neointimal hyperplasia and luminal stenosis are the keys to the development of VAT. 1 Mounting evidence has shown that VAT is associated with an increase in systemic inflammation markers, such as C-reactive protein (CRP) 2 and homocysteine, 3,4 in chronic HD patients. An increase in inflammatory markers, such as macrophages, lymphocytes, vascular cell adhesion molecule-1, tumor necrosis factor-a and interleukin-6, is found on primary stenotic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the traditional view, neointimal hyperplasia and luminal stenosis are the keys to the development of VAT. 1 Mounting evidence has shown that VAT is associated with an increase in systemic inflammation markers, such as C-reactive protein (CRP) 2 and homocysteine, 3,4 in chronic HD patients. An increase in inflammatory markers, such as macrophages, lymphocytes, vascular cell adhesion molecule-1, tumor necrosis factor-a and interleukin-6, is found on primary stenotic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, two recent studies showed that patients with very low homocysteine plasma levels had worse outcomes including a higher incidence of hospitalization and mortality [7, 8]. This raises the question as to whether elevated homocysteine in uremic patients is consequential rather than causal in the role of cardiovascular complications [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Bowden et al showed in both a retrospective study of 114 patients15 and in a prospective study of 185 patients16 that chronically high homocysteine levels in patients with end-stage renal disease were not associated with an increased incidence of VAT. A retrospective Taiwanese study conducted by Chen et al in 196 patients on chronic hemodialysis showed no relationship between homocysteine and VAT 17. Manns et al found no association between homocysteine levels or anticardiolipin antibody and VAT in a cross-sectional study involving 118 patients 3.…”
Section: Discussionmentioning
confidence: 96%